Influence of soil and tire parameters on traction - M. Schreiber; H.D. Kutzbach (Research in Agricultural Engineering, 2008)
The drawbar pull, travel reduction (slip), and rolling resistance are the main criteria to describe the traction behaviour of off road vehicles. Besides the engine performance, the drawbar pull is influenced by the traction conditions such as soil and the tire parameters. These traction conditions have to be described by a limited number of parameters which can be easily determined. Empirical equations were used to analyse roughly 850 traction curves measured and published by Steinkampf. As a result, the important parameters to describe the traction conditions are three tire parameters (radius, width, inflation pressure) and five soil parameters (soil cover, upper soil strength, lower soil strength, clay content, moisture content). These parameters with relative values between 0 and 100% are used to establish the equations for the traction prediction. Main steps to achieve this goal are the extension of the traction slip equation by a linear term of slip, and the description of this curve by 4 meaningful characteristic coefficients: the x- and y-coordinates of the κ-maximum (σ κmax, κmax), the y-axis intercept ρe, and the gradient of κ at zero slip (κ'(0)).